High load capacity spur gears with conchoidal path of contact - Tkach Pavlo (EDP Sciences, 2021)
The present study is devoted to investigation of spur gears with a conchoidal path of contact and a convex-convex contact between teeth. The load capacity and energy efficiency were evaluated using both theoretical and experimental approaches. The theoretical analysis showed that the conchoidal gear pairs are 5–21% stronger in terms of contact stress and have similar energy efficiency as compared to the involute gear pairs of the same configuration. Experiments were conducted on a gear test rig. Its energy efficiency was determined by measuring the active power of the motor driving the pinion shaft and controlling the torque at the gear shaft. The load capacity of the tested gear pair was estimated by analysing changes in the energy efficiency. It was found that the conchoidal gear pair has more than 20% higher load capacity and slightly higher energy efficiency, which agrees well with the mentioned theoretical results. Thereby, the study concludes a substantially higher load capacity of the conchoidal gears compared to the traditional involute ones.